Stakeholders’ Pressure on Carbon Neutrality. The Role of Environmental Leadership and Green Finance - Kuddus, Md. Ruhul; Hasan, Md. Mahedi; Islam, Md. Shajul; Hossain, Mohammad Kamal (International Journal of Economics and Financial Issues, 2026)
This study aims to examine the influence of stakeholders’ pressure on carbon neutrality and the role of environmental leadership and green finance. Data were collected from 451 front-line employees from small and medium manufacturing firms through a judgmental sampling technique, using a Likert-scale questionnaire administered in face-to-face surveys. Hypothesis testing was conducted by means of PLS-SEM (Partial Least Squares-Structural Equation Modeling). The findings revealed that stakeholder pressure significantly influences carbon neutrality. Stakeholders also influence the adoption of green finance and the form of environmental leadership in a firm. Green finance and environmental leadership have a positive and significant impact on carbon emissions. The study discovered that green finance and environmental leadership mediate the relationship between stakeholder pressure and carbon neutrality. Finally, both green finance and environmental leadership serially mediate the relationship between stakeholders’ pressure and carbon neutrality. This study shows how different kinds of stakeholders in Bangladesh respond to carbon neutrality and the beneficial effects of green financing and environmental leaders on carbon neutrality, which have not been covered by another research.